RANCANG BANGUN SISTEM PAYUNG OTOMATIS BERBASIS INTERNET OF THINGS - I Made Agus Calvin Ardhana Putra; I Putu Agus Eka Saputra; I Gusti Agung Putu Raka Agung; Anak Agung Ngurah Amrita (Jurnal SPEKTRUM, 2025)
This study designs an Internet of Things (IoT)-based automatic umbrella system that can be operated manually or automatically via the Blynk application. The process begins with device initialization, including the configuration of the ESP32, servo motor, rain sensor, RTC, push button, and switch. The device then connects to a Wi-Fi network to enable data transmission and reception. In manual mode, the user can open or close the umbrella using a physical button or commands from Blynk. In automatic mode, the system follows a preset schedule: the umbrella opens from 08:00 to 16:00, remains open from 16:00 to 22:00 if rain is detected, and closes from 22:00 to 08:00. Data such as servo position, umbrella status, time, and operation mode are sent to Blynk in real time. Test results indicate that the system functions according to the design, provides ease of use, and helps protect.